The Adventure is to Discover Ourselves: Theoretical and Methodological Reflections for a Feminist Education and History "from the Other Corner" - Abarca Salinas, María Elena (2022)
From the recognition of some historical experiences from feminist activists and experiences of personal political activism, notes, reflections, and proposals are proposed —as clues— about a feminist education, from educational spaces and formal classrooms and non-school training spaces, maybe not academic, but activist politics. What are the implications of a feminist education? In what way can we think and propose a history about women in the classroom? What civilizing project do we need to know and involve, from the everyday, the intimate, the private and the public? These are some questions, by way of invitation, that guide this article.